2006
DOI: 10.1021/jp056003l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Solutes on the Hydrogen Bond Network Dynamics of Water:  Power Spectral Analysis of Aqueous NaCl Solutions

Abstract: To understand the modifications of the hydrogen bond network of water by ionic solutes, power spectra as well as static distributions of the potential energies of tagged solvent molecules and solute ions have been computed from molecular dynamics simulations of aqueous NaCl solutions. The key power spectral features of interest are the presence of high-frequency peaks due to localized vibrational modes, the existence of a multiple time scale or 1/falpha frequency regime characteristic of networked liquids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…In a series of recent papers, we showed that power spectral analysis could be used to understand the connections between the local order, hydrogen bond network dynamics and the kinetic anomalies in water 14,15,16,17,18,19 . The power spectral density of an observable A(t) as a function of time t is defined as follows 20 :…”
mentioning
confidence: 99%
“…In a series of recent papers, we showed that power spectral analysis could be used to understand the connections between the local order, hydrogen bond network dynamics and the kinetic anomalies in water 14,15,16,17,18,19 . The power spectral density of an observable A(t) as a function of time t is defined as follows 20 :…”
mentioning
confidence: 99%
“…It is possible to build mixtures of several components, solvate proteins, and build ordered arrangements as double layers or micelles. [20][21][22][23][24][25][26][27] Further improvements of the package may include macro-input keywords to build the most common systems and more complex unit cells, the parallelization of tasks other than function and gradient evaluation, the improvement of global convergence heuristics, and the development of a graphical user interface, or its incorporation as a plugin into some graphical molecular viewer.…”
Section: Discussionmentioning
confidence: 99%
“…This definition of binding energy is identical to the tagged potential energy (TPE) of the molecule, u, where the sum is over interactions of the tagged species with all others. 11,21,22,24 When the interactions in the system are pairadditive, then one can write that U ) (0.5/N)∑ i u i , where the index i runs over all atoms in the system. The molecular tagged potential energy requires a summation over all constituent atoms of a molecule.…”
Section: Observables Local Structural Ordermentioning
confidence: 99%